1969
DOI: 10.1037/h0026669
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory intensity-difference thresholds in the pigeon.

Abstract: The methods of single stimuli and constant stimuli were used with a modified conditioned suppression technique to determine olfactory intensity-difference thresholds in White Carneaux and White King pigeons. While responding for grain reinforcement on a VI 2-min. schedule, conditioned suppression was established in the birds after several sessions by pairing amyl acetate odor at 7% of vapor saturation with electric shock. The degree of suppression to nonshocked lower intensities of this odor determined the DLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Instead, it may reflect an ability to accurately discriminate among odors of different types (Adrian 195 1, Bang 197 1). Domestic pigeons (Columba livia), with a bulbto-hemisphere ratio in the middle range (18%; Bang 1971), discriminate odors in laboratory experiments (Shumake et al 1969) and appear to use scent as one of the cues for homing (Papi et al 1973(Papi et al , 1978Benvenuti et al 1973;Wald-Vogel et al 1978). Members of a species with small olfactory bulbs may be sensitive to particular odors important to their survival.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it may reflect an ability to accurately discriminate among odors of different types (Adrian 195 1, Bang 197 1). Domestic pigeons (Columba livia), with a bulbto-hemisphere ratio in the middle range (18%; Bang 1971), discriminate odors in laboratory experiments (Shumake et al 1969) and appear to use scent as one of the cues for homing (Papi et al 1973(Papi et al , 1978Benvenuti et al 1973;Wald-Vogel et al 1978). Members of a species with small olfactory bulbs may be sensitive to particular odors important to their survival.…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive anatomical survey of 15 1 species in 23 orders, Bang and Cobb (1968) and Bang (197 1) measured the relative diameters of the olfactory bulb and ipsilateral hemisphere, finding a 12-fold variation in the ratio of these dimensions. Behavioral studies on Rock Doves (Columba livia; Michelsen 1959, Henton et al 1966. Shumake et al 1969.…”
mentioning
confidence: 99%
“…Michaelson (16) demonstrated that pigeons can discriminate between the presence and absence of olfactory stimuli. The pigeon's absolute detection threshold and thresholds for the detection of differences in stimulus intensity have now been described (17)(18)(19)(20). Much of this work has been done using conditioned suppression, a technique whose application to animal psychophysics has been reviewed (21).…”
Section: Odors As Discriminative Stimuli Olfactory Psychophysicsmentioning
confidence: 98%